Progress of anti-tuberculosis drug targets and novel therapeutic strategies - Zhang, Yang; Wu, Ruiying; Sun, Mingrui; Li, Xiaotian; Fang, Ren; Xing, Jiayin; Li, Zhaoli; Wen, Yurong; Song, Ningning (Frontiers in Microbiology, 2025)
Tuberculosis, a chronic infectious disease caused by Mycobacterium tuberculosis complex, has re-emerged as the leading cause of death worldwide as a single infectious agent. The increasing prevalence of multidrug-resistant tuberculosis and extensively drug-resistant tuberculosis poses a severe and growing threat to global health. Therefore, it is urgent to find new drug targets. Recently, significant advancements have been made in the research of drug targets and novel therapeutic strategies for tuberculosis. This review summarizes recent processes on anti-tuberculosis drug targets, such as cell wall synthesis, nucleic acid replication and transcription, energy metabolism, and ferroptosis. Furthermore, this review summarizes the research progress of three innovative tuberculosis treatment strategies, including antimicrobial peptides, host-directed therapies, and nanoparticle-based drug delivery systems, aiming to provide a theoretical foundation and new research perspectives for the clinical development of new drugs.